2014
DOI: 10.1007/s13187-014-0716-9
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Cervical Cancer Screening Among US Hispanics/Latinas: A Qualitative Systematic Review

Abstract: Purpose Hispanic/Latina women experience the highest cervical cancer incidence rates of any racial/ethnic group in the United States (US), and tend to present with more severe cases and experience higher mortality compared to most other populations. The goal of this qualitative systematic review was to explore existing interventions to increase cervical cancer screening among US Hispanics/Latinas and to identify characteristics of effective interventions and research gaps. Materials and Methods Six online da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 92 publications
(373 reference statements)
0
41
0
Order By: Relevance
“…1–3 Although routine Pap test screening has been proven to reduce cervical cancer incidence and mortality rates, 4 Hispanic women along the Texas-Mexico border encounter both individual- and system-level barriers to Pap test screening. 5 Individual barriers 5 include a lack of comprehension of what cervical cancer is and how it can be prevented, low self-efficacy when communicating with medical providers, and attitudes/beliefs such as embarrassment, fear, and fatalism. System-level barriers 5, 6 include lack of health insurance coverage, lack of culturally and linguistically competent care, lack of transportation infrastructure, limited child care options, illegal immigrant status, and fewer health care providers in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…1–3 Although routine Pap test screening has been proven to reduce cervical cancer incidence and mortality rates, 4 Hispanic women along the Texas-Mexico border encounter both individual- and system-level barriers to Pap test screening. 5 Individual barriers 5 include a lack of comprehension of what cervical cancer is and how it can be prevented, low self-efficacy when communicating with medical providers, and attitudes/beliefs such as embarrassment, fear, and fatalism. System-level barriers 5, 6 include lack of health insurance coverage, lack of culturally and linguistically competent care, lack of transportation infrastructure, limited child care options, illegal immigrant status, and fewer health care providers in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Since Hispanics/Latinos represent the largest ethnic minority group in the U.S., efforts to improve cervical cancer prevention among this population will have a significant public health impact on incidence and mortality rates [28]. There exists variability in cervical cancer incidence and mortality rates among Hispanic/Latino subgroups, with higher rates as well as greater barriers to screening among newer immigrant Hispanic/Latina women in the Midwest, Southeast, and those living near the United States-Mexico border region, all of whom are primarily of Mexican origin [36, 32, 21]. Research has shown that some Hispanic/Latino groups such as Puerto Ricans and Cubans have higher screening rates than Mexican Americans [1].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 90% of the farmworkers in the study area – southeast Georgia – are men [19]. However, farmworker women are an understudied group with regard to cancer incidence and mortality, and there is limited evidence demonstrating the effectiveness of cervical cancer screening interventions targeting this population [4, 21]. The vast majority of farmworkers in the U.S. are of Mexican origin, and more than half are undocumented [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through this study, we built on our partnership’s experiences with Latina sexual and reproductive health (Cashman, Eng, Simán, & Rhodes, 2011; Mann, Foley, Tanner, Sun, & Rhodes, 2014; Rhodes et al, 2012) and with HoMBReS, HoMBRES-2, and HoMBReS Por un Cambio, efficacious interventions designed to reduce HIV risk among Spanish-speaking Latino men in NC (Rhodes, 2012). …”
mentioning
confidence: 99%